JUST A GRAZE?. Issue 11 (9th October 2013) - Doshi, Anisha; Dahdalleh, Dima; Warrell, Clare; Kullmann, Dimitri
Abstract : We describe a case of a diagnostically difficult stroke mimic, cephalic tetanus. 1 Currently there are 12–15 cases of tetanus reported annually in the United Kingdom, 2 but worldwide it accounts for one million deaths, 80% being in Africa and South East Asia. 3 Tetanus is caused by infection with clostridium tetani. 4 5 Cephalic Tetanus is defined as a combination of trismus and paralysis of one or more cranial nerves, most commonly the facial nerve. It is rare, 0.9–3% of all tetanus cases, and has a high mortality of between 15–30% if it progresses to generalised tetanus. 1 A 76 year old right handed lady presented to the stroke unit with sudden onset of swallowing difficulty, speech impairment and left sided facial weakness on waking. She had multiple vascular risk factors, however on examination her signs had resolved. Of note she had a sutured right supraorbital laceration sustained a week prior to presentation following a road traffic accident. Computed tomography (CT) showed no acute stroke and confirmed the presence of a large supraorbital haematoma. She was treated with a combination of high dose aspirin and prednisolone therapy for a presumed left sided transient ischaemic attack and a right sided Bell's palsy. During the next few days the patient had labile blood pressure and heart rate readings, complained of difficulty opening her jaw, and had intermittent episodes of laryngeal episodes. Her admission CT was reviewed and note was made of a 3 mm metallic fragment and locules of gas within her haematoma. A clinical diagnosis of cephalic tetanus was made and this was later confirmed on wound culture isolates. As highlighted by our case, ptosis and cranial nerve palsies may precede trismus in cephalic tetanus, and only two published case reports in Korea describe this order of presentation worldwide. 1 The spore–forming motile gram positive bacillus Clostridium tetani 4 5 is rarely isolated and therefore the diagnosis is clinical. Two toxins are produced; Tetanolysin which damages surrounding viable tissue, and Tetanospasmin which inhibits GABA and glycine presynaptic release leading to the clinical syndrome of: rigidity, muscle spasms and autonomic dysfunction. 3 Management is based on three principles; preventing further toxin release with debridement and antibiotics, neutralising toxin present outside of the Central Nervous System (CNS) with tetanus immunoglobulin, and minimising the effects of the toxins in the CNS with early anaesthetic support. 4 5 All patients require full tetanus toxoid immunisation post–infection. 1 5 In conclusion, when approaching a patient with head injury and one or more cranial nerve palsies, it is important to consider cephalic tetanus. Figure 1 Axial CT head shows a large subcutaneous haematoma overlying the right frontal convexity with locules of gas and a 3mm metallic density at its inferior aspect, possibly representing a foreign body.